DOES VISCERAL FAT A RISK FACTOR ASSOCIATE WITH BONE DENSITY OF BACK PAIN PATIENTS IN LUMBAR DISC DEGENERATION? - C K Sreeja; V N Meena Devi; M K Aneesh; Sreekanth K S (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: The impact of obesity and excess of visceral fat has been linked to bone metabolism. The objective of the study was relationship between visceral fat and bone density (BD) on back pain subjects with disc degeneration.Methods: A total of 197 low back pain subjects between 30-70 years, undergone lumbosacral MRI (1.5T) were included. Based on MRI report, subjects were grouped into disc bulging (DBG) and Nerve compression Group (NCG) depending on degree of degeneration. Body fat were analysed by bioelectrical impedance analysis. Depending on the fat distribution, subjects were also subdivided into normal, overfat and obese.Results: The result showed that in disc bulging patients there was a signiﬁcant correlation between visceral fat with bone density and it was statistically significant (p=0.0002). In nerve compression group (NCG), visceral fat and bone density were statistically highly significant (p=0.000).Conclusion: The degree of increment of  visceral fat has a negative effect on bone density. So body composition analysis is of utmost importance in clinics for the preservation of bone health and severity of degeneration.